2016
DOI: 10.1177/1540796915621190
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Severe Disabilities and Complex Health Care Needs

Abstract: This case study examined one high school student's access to inclusive education and experiences in an inclusive English class after he acquired severe disabilities and complex health care needs from a nontraumatic brain injury. Multiple sources of data (i.e., interviews, field notes, and documents) were collected and analyzed to formulate understanding of the unique particularities of this intrinsic, naturalistic case. Findings were organized into four major themes: (a) school reentry and adjustment, (b) comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…All EC directors surveyed (100%) reported that these students are provided with Individualized Health Plans. Given these findings, it is apparent that districts are currently following the recommendation that students are provided with formal school services at some level following reentry (Ballard & Diamond, ; Hopkins & Hughes, ; Shaw & McCabe, 2008). Within the context of these plans, participants indicated that students are most often provided with the following accommodations/modifications: extra time for assignments, hospital–homebound services, and classroom/testing accommodations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All EC directors surveyed (100%) reported that these students are provided with Individualized Health Plans. Given these findings, it is apparent that districts are currently following the recommendation that students are provided with formal school services at some level following reentry (Ballard & Diamond, ; Hopkins & Hughes, ; Shaw & McCabe, 2008). Within the context of these plans, participants indicated that students are most often provided with the following accommodations/modifications: extra time for assignments, hospital–homebound services, and classroom/testing accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Planning for eventual school reentry should begin immediately upon recognition that the student will face an extended absence as a result of their chronic health condition (Kaffenberger, ). Moreover, past research has shown that if the school reentry process becomes delayed for the student experiencing a chronic health difficulty, the student is then more likely to experience difficulties upon their return including reduced access to inclusive education (Ballard & Dymond, ). The beginning stages of this process, at the very least, should include making contact with the student's family to assess the level of family support needed while the child is away, informing the family of school services that can be implemented before their child returns to school (e.g., homebound instruction), and notifying them of potential services their child might be entitled to as he/she returns to the school setting (Kaffenberger, ; Shaw & McCabe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of information, we had to be cautious in considering them fully inclusive. The remaining three studies (Alexandersson, 2011;Ballard & Dymond, 2016;Feldman, Carter, Asmus, & Brock, 2016) explicitly described the effective participation in academic activities of students with disabilities and clarified that inclusion was only partial (e.g. percentage of school day or number/type of classes attended).…”
Section: Contexts Of Inclusion and Participantsmentioning
confidence: 99%
“…No differences were found in progress in mathematics, according to Dessemontet et al (2012). The other two studies included in this category (Ballard & Dymond, 2016;Harkins, 2013) were case studies in which narrative information was provided on students' achievements, revealing a general satisfaction in academic performance.…”
Section: Learning Outcomesmentioning
confidence: 99%
See 1 more Smart Citation